Raising Job Quality and Worker Skills in the US: Creating More Effective Education and Workforce Development Systems in States - Harry J. Holzer (Institute for the Study of Labor (IZA), 2012)
To improve the employment rates and earnings of Americans workers, we need to create more coherent and effective education and workforce development systems, focusing primarily (though not exclusively) on disadvantaged youth and adults, and with education and training more clearly targeted towards firms and sectors providing good-paying jobs. This paper proposes a new set of competitive grants from the federal government to states that would fund training partnerships between employers in key industries, education providers, workforce agencies and intermediaries at the state level, plus a range of other supports and services. The grants would especially reward the expansion of programs that appear successful when evaluated with randomized control trial techniques. The evidence suggests that these grants could generate benefits that are several times larger than their costs, and would therefore lead to higher earnings and lower unemployment rates among the disadvantaged.
Keywords: J2; J3; J6; J08; 330; education; workforce development; jobs; skills; employment; Berufsbildung; Weiterbildung; Subvention; Beschäftigungseffekt; Qualifikation; USA